2022
DOI: 10.3389/fmicb.2022.778512
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Instant Coffee and Decaffeinated Coffee on the Gut Microbiota and Depression-Like Behaviors of Sleep-Deprived Rats

Abstract: ObjectiveBased on our previous research, chronic paradoxical sleep deprivation (PSD) can cause depression-like behaviors and microbial changes in gut microbiota. Coffee, as the world’s most popular drink for the lack of sleep, is beneficial to health and attention and can eliminate the cognitive sequelae caused by poor sleep. The purpose of this study is to investigate the effects of coffee and decaffeinated coffee on PSD rats.Research Design and MethodsA total of 32 rats were divided into four groups: control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 113 publications
1
10
0
Order By: Relevance
“…Various studies have suggested that Proteobacteria is a Gram-negative bacteria that is commonly overrepresented in several intestinal diseases and causes a decrease in intestinal mucus, which triggers the impaired intestinal barrier and low-grade inflammation [ 51 , 52 ]. In our results, similar to the previous studies, the abundance of pro-inflammatory bacteria Proteobacteria was significantly decreased after the CISR treatment, suggesting that a sleep restriction may not induce gut dysbiosis and inflammatory responses through this microbial pathway [ 53 ]. Actinobacteria is widely used as probiotics, demonstrating beneficial effects on numerous pathological conditions, and they are critical in the maintenance of gut homeostasis, the modulation of gut permeability, the immune system, and gut–brain axis [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Various studies have suggested that Proteobacteria is a Gram-negative bacteria that is commonly overrepresented in several intestinal diseases and causes a decrease in intestinal mucus, which triggers the impaired intestinal barrier and low-grade inflammation [ 51 , 52 ]. In our results, similar to the previous studies, the abundance of pro-inflammatory bacteria Proteobacteria was significantly decreased after the CISR treatment, suggesting that a sleep restriction may not induce gut dysbiosis and inflammatory responses through this microbial pathway [ 53 ]. Actinobacteria is widely used as probiotics, demonstrating beneficial effects on numerous pathological conditions, and they are critical in the maintenance of gut homeostasis, the modulation of gut permeability, the immune system, and gut–brain axis [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, caffeine has been demonstrated to exhibit anti-inflammatory effects at low concentrations and pro-inflammatory effects at high levels by inhibiting or activating cytokines [ 59 ]. As for the role of caffeine in sleep restriction, it has been suggested to exert a neuroprotective effect, meliorate the dysbiosis of gut microbiota, and reduce the levels of proinflammatory factors in serum [ 53 , 60 ]. Considering the above effects, we do not deny the possible beneficial effects of caffeine, but the inopportune use of caffeine in our CISR model caused negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…SD has become a health problem in the modern society. By definition, sleeping less than 6 h for six consecutive nights is considered chronic SD ( 28 ). In this study, we applied paradoxical sleep, bright light, and noise to build the RM SD model.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin and its glycosides, which are present not only in coffee but also in tea and fruits, increased the abundance of Akkermansia , Bacteroides , Parabacteroides , and Ruminococcus in rats fed a high-fat sucrose diet [ 98 ]. Wistar rats orally administered soluble caffeinated or decaffeinated coffee solution showed an increase in the abundance of Firmicutes and Bacteroidetes compared to the control group [ 99 ]. Similarly, in Wistar rats with diet-induced metabolic syndrome, coffee pulp application led to a decrease in the Firmicutes/Bacteroidetes ratio and an increase in gut microbiota diversity [ 100 , 101 ].…”
Section: Prebioticsmentioning
confidence: 99%